2020
DOI: 10.3390/cells9112408
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutational Status, Spheroid Formation, and Drug Response of a New Genomically-Stable Human Ovarian Clear Cell Carcinoma Cell Line, 105C

Abstract: Ovarian clear cell carcinoma (OCCC) is a rare subtype of gynecological cancer for which well-characterized and authenticated model systems are scarce. We provide an extensive characterization of ‘105C’, a cell line generated from an adenocarcinoma of the clear cell histotype using targeted next-generation sequencing, cytogenetic microarrays, along with analyses of AKT/mTOR signaling. We report that that the 105C cell line is a bona fide OCCC cell line, carrying PIK3CA, PTEN, and ARID1A gene mutations, consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…The shift from adherent to spheroid cells during EOC metastasis has previously been reported to be AKT-dependent [ 2 , 38 , 39 , 40 ], and spheroid cells are characterized by low S473 phosphorylation levels on AKT [ 2 , 38 ]. We previously showed that T308 phosphorylation is the primary determinant for AKT1 activity [ 6 , 7 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The shift from adherent to spheroid cells during EOC metastasis has previously been reported to be AKT-dependent [ 2 , 38 , 39 , 40 ], and spheroid cells are characterized by low S473 phosphorylation levels on AKT [ 2 , 38 ]. We previously showed that T308 phosphorylation is the primary determinant for AKT1 activity [ 6 , 7 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…ES-2 used in a previous report [32] showed mutations only in NOTCH3, similar to RMG-I. In OCCC, a combination of mutations in ARID1A and PIK3CA is more frequent [40] because metformin was found to be effective in both OVISE, which has these mutations, and RMG-I, which does not. This highlights the possibility of using metformin as an antitumor drug targeting OCCC.…”
Section: Discussionmentioning
confidence: 79%
“…The strength of this study lies in its demonstration of the antitumor effects of metformin in several OCCC cell lines with different genetic mutation patterns. The OCCC cell lines used in this study were tested for genetic mutations as described by Kashiyama et al and Kolendowski et al [39,40]. To summarize the two reports, RMG-I showed mutations only in NOTCH3, OVISE had mutations in ARIDA and PIK3CA.…”
Section: Discussionmentioning
confidence: 99%
“…According to the comprehensive list of OCCC cell lines provided by Franklin et al [ 12 ] and to the establishment of the 105C cell line [ 13 ], 29 OCCC cell lines have been established so far and some of them are able to generate tight spheroids when cultured in non-adherent conditions [ 14 ]. Nevertheless, most of them have not been extensively characterized and less than half of them have been deposited in cell banks.…”
Section: Introductionmentioning
confidence: 99%